CONSIDERACIONES EN TORNO A LAS IMPLICACIONES METAFÍSICAS VIRGILIANAS EN GIORDANO BRUNO (Stylos, 2021)
The central purpose of the present work is to give an account of the meaning of the reference to the passage of the katábasis of Aeneas, found in Aeneid VI 724-727, on metaphysical aspects of Giordano Bruno’s work. To accomplish this, two previous objectives are taken into account: first, analyzing certain passages of Virgil's work, raising the possibility of conceiving a Virgilian philosophy and, secondly, making a journey on the reception and transformation of meaning around Aeneid VI 724-727 from the 1st to the 15th century in order to register milestones in the reception of this passage until reaching Giordano Bruno. When analyzing the works of this author in relation to the aforementioned passage, we try to account for its relevance in Nolan’s work.
Keywords: Virgil – Giordano Bruno – Aeneid – mens – spiritus.